Associations among parental mental health, lifestyle factors and infant mortality in rural and urban mothers - Shah, S. Mudasser; Zhang, Zijin; Jahangir, Muhammad; Alharbi, Fatimah Sayer; Zhang, Wenrui; Lin, Xiuyun (Frontiers in Public Health, 2025)
BackgroundInfant mortality remains a critical public health concern, necessitating a comprehensive understanding of its determinants. This investigation aimed to examine associations between social determinants, lifestyle factors, and maternal mental health in relation to infant mortality.MethodsA cross-sectional survey was conducted among 500 mothers (250 rural, 250 urban) in Khyber Pakhtunkhwa (KPK), Pakistan. The Depression Anxiety Stress Scales (DASS-21) were employed to evaluate symptoms of anxiety, depression, and stress, while a Lifestyle and Habits Questionnaire collected data on physical activity and dietary patterns. Data was collected via questionnaires and demographic information from 500 mothers using purposive sampling. Key variables included rural/urban residence, age at marriage, socio-economic status, access to healthcare, type of delivery attendant, and under-5 mortality rates.ResultsRural mothers had significantly lower infant mortality rates (p = 0.000) compared to urban mothers. Physical activity and diet were negatively correlated with depression, anxiety, and stress (p < 0.05). Rural mothers reported higher physical activity (M = 23.46 vs. 21.79, p = 0.001) and healthier diets (M = 16.01 vs. 14.85, p = 0.001). Urban mothers exhibited significantly higher levels of depression (M = 6.59 vs. 1.63, p = 0.000), anxiety (M = 7.68 vs. 2.18, p = 0.000), and stress (M = 9.65 vs. 2.32, p = 0.000). Early marriage was linked to increased anxiety and stress (p = 0.000).ConclusionFindings underscored the importance of addressing social determinants and fostering healthy lifestyles to improve maternal and child health outcomes. Interventions that promote access to healthcare, physical activity or healthy dietary habits can help make the infant mortality rates and the overall state of health of the mother better.